Advances in food and nutrition research. - Kinsella, John E., 1938-; Taylor, Steven L. (Advances in food and nutrition research, 1995)
Advances in Food and Nutrition Research recognizes the integral relationship between the food and nutritional sciences and brings together outstanding and comprehensive reviews that highlight this relationship. Contributions detail the scientific developments in the broad areas encompassed by the fields of food science and nutrition and are intended to ensure that food scientists in academic and industry as well as professional nutritionists and dieticians are kept informed concerning emerging research and developments in these important disciplines. Key Features * This volume includes three thematic chapters: * The Role of Flavoring Substances in Food Allergy and Intolerance * The Use of Amino Acid Sequence Alignments to Assess Potential Allergenicity of Proteins Used in Genetically Modified Foods * Sequence Databases for Assessing the Potential Allergeniticity of Proteins Used in Transgenic Foods.